Research of the Influence of Roller Shape on the Vibration Characteristic of Mecanum Wheel - Jin Lei; Qin Xunpeng; Hua Lin; Liu Huaming; Zhang Jiang (Jixie chuandong)
In order to study the influence of the roller shape on the dynamics performance of the Mecanum wheel,the design method of the Mecanum wheel roller contour is firstly proposed,and then the parametric model of the Mecanum wheel is established. The motion processing of the Mecnaum wheel is simulated based on ADAMS. The movement characteristics of the Mecanum wheel with the designed roller are obtained,and the influence of different roller shapes on the dynamics performance of Mecanum wheel is compared and analyzed in detail. The results provide the subsequent vehicle motion control and trajectory planning with original data,and have certain guiding significance for improving the motion stability of the omni-directional mobile vehicle.